2016
DOI: 10.1159/000453218
|View full text |Cite
|
Sign up to set email alerts
|

MiR-155 is Involved in Renal Ischemia-Reperfusion Injury via Direct Targeting of FoxO3a and Regulating Renal Tubular Cell Pyroptosis

Abstract: Background/Aims: Ischemia/reperfusion injury (IRI) plays a crucial role in renal transplantation and can cause renal failure associated with pyroptosis, a pro-inflammatory-induced programmed cell death. Small endogenous non-coding RNAs have been shown to be involved in renal ischemia/reperfusion injury. This study was performed to investigate which miRNAs regulate pyroptosis in response to renal ischemia/reperfusion injury and determine the mechanism underlying this regulation. Methods: An in vivo rat model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 51 publications
1
74
0
Order By: Relevance
“…Therefore, caspase-1 dependence is a definitive feature of pyroptosis that is characterized by the release of pro-inflammatory contents and plasma membrane rupture. Recent studies have demonstrated that pyroptosis mediated the death of renal and cardiac cells, leading to kidney and heart failure [11, 12, 43]. Our findings were consistent with those previously reported results.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Therefore, caspase-1 dependence is a definitive feature of pyroptosis that is characterized by the release of pro-inflammatory contents and plasma membrane rupture. Recent studies have demonstrated that pyroptosis mediated the death of renal and cardiac cells, leading to kidney and heart failure [11, 12, 43]. Our findings were consistent with those previously reported results.…”
Section: Discussionsupporting
confidence: 94%
“…Its activation by danger signals can mediate the maturation of capase-1, which results in the conversions of precursors of interleukin-1β and 18 into their active forms [10]. Recent researches further demonstrated that pyroptosis mediated the death of renal tubule epithelial cells after renal ischemia reperfusion injury [11, 12]. Therefore, it is of great significance to understand the mechanism that suppresses the inflammatory response and is responsible for the pyroptosis inhibition during the development and progression of cerebral ischemia injury.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are endogenous, small non-coding RNAs which are ∼22 nucleotides in length, and are involved in the post-transcriptional regulation of genes. Functional changes, including up-regulation and down-regulation of miRNAsare known to be involved in the pathogenesis of many diseases such as myocardial infarction [6-9], coronary artery calcification (CAC) [10], arrhythmia [11], cardiomyocyte hypertrophy [12-13], heart failure [14], renal ischemia-reperfusion injury [15], non-alcoholic fatty liver disease [16], tuberculosis [17], pancreatic ductal adenocarcinoma [18], and diabetes mellitus [19]. miRNAs are reported to not only exist within the cell but also reside stably in the extracellular compartments such as the circulation, which enables relatively simple detection of miRNAs as disease biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…The improved function was associated with a reduced amount of tubular damage and decreased expression of pro-inflammatory molecules, including IL-18. IL-18 is well known to contribute to the worsening of renal injury induced by IRI, whereas TNF-α is an important mediator in the causation and perpetuation of previously observed kidney injury [56-58]. …”
Section: Discussionmentioning
confidence: 99%